PENGARUH ALELOPATI BERDASARKAN TINGKAT KEDALAMAN TANAH PADA LAHAN ALANG-ALANG TERHADAP KEBERADAAN SEED BANK DAN PERTUMBUHAN KACANG TANAH - Bangsa, Astuti H.; Abdullatif, Zauzah; Soenarsih, Sri (Universitas Khairun, 2023)
The Bukit Tinggi Village area, Malifut District, North Halmahera Regency has open land with hilly topography dominated by reed vegetation. The research aims to determine the diversity of weeds in marginal land areas in Bukit Tinggi Village, Malifut District, North Halmahera. Knowing the effect of different soil depth levels on seed bank growth. Knowing the potential for cultivating peanut plants on marginal land overgrown with reeds. This research lasted for 3 months starting from October to December 2022, taking place in the Green House and the Faculty's practice area. Agriculture by taking soil samples for weed seed bank testing comes from alang-alang land in the Bukit Tinggi Village area, Malifut District, North Halmahera Regency. This research uses a Completely Randomized Design (CRD) consisting of 3 treatments with 4 replications at each sample point so that There are 12 treatment units in each plot. The sample point plot consists of 4 points, namely east, west, north and south in the alang-alang field. The total sample is 48 sample units. Each sample consists of 3 depths consisting of: K1 = soil depth 0-10 cm from the ground surface K2 = soil depth 10-20 cm from the ground surface, K3 = soil depth 20-30 cm from the ground surface. The conclusion of this research is that different soil depths in the alang-alang meadow area influence the existence of weed seed banks in Bukit Tinggi Village, Malifut District, North Halmahera. Different soil depths in the alang-alang meadow area influence height growth and number of branches. , number of pods, wet weight and dry weight of peanut plants. The best soil depth for cultivating peanuts on marginal land covered with reeds is 20-30 cm deep.Â Key words: , Alang-alang, allelopathy marginal land, peanuts, soil depth,